Variations in Optic Cup to Disc Ratio Due to Refractive Errors and Smoking - Mukhtar, Sahrish; Asma Basharat Ali; Nadia Younus; Madeeha Sadiq; Alina Atif; Nuzhat Hassan (Journal of University College of Medicine and Dentistry, 2024)
Objective: To evaluate the deviation of Optic Cup to Disc Ratio with refractive errors and smoking status. Methodology: This was a cross-sectional observational study carried out from January to October, 2016 at Dr Akil bin Abdul Kadir Institute of Ophthalmology,Karachi, Pakistan. A total of 300 eyes of 300 patients were included in the study and divided according to the error of refraction into emmetropic (n=135), hypermetropic (n=77) and myopic (n=88) eyes for Cup to Disc Ratio measurements. To assess the effect of smoking, emmetropic eyes were further divided into smokers (n=23) and nonsmokers (n=112). Independent T test and ANOVA was used to analyze the differences in the mentioned groups. P value <0.05 was taken as significant. Results: The optic Cup to Disc Ratio in emmetropic eyes was found to be 0.27 ± 0.03. It was found to be significantly decreased in myopic eyes (0.24 ± 0.05) and significantly increased in hypermetropic eyes (0.31 ± 0.07) with p value = 0.01. CDR was significantly increased in smokers (0.31 ± 0.07) than nonsmokers (0.26 ± 0.01) with p value of 0.01. These findings will aid the clinicians in diagnosing and treating different ophthalmic diseases involving the optic cup. Conclusion: Cup to Disc Ratio was significantly increased in myopic eyes and significantly decreased in hypermetropic eyes compared to emmetropic eyes. Smokers and nonsmokers also showed significant variations in CDR. This study concludes that the cup to disc ratio is significantly affected by the refractive errors and smoking status.